Identification of Defects in Fruits Using Digital Image Processing - Arunachalam, Siddhika; Kshatriya, Harsh H; Meena, Mamta (International Journal of Computer Sciences and Engineering, 2025)
Image Processing is a technique which converts an image into a digital image to obtain some enhancement or to select some effective information from it. Classification of fruit quality or grading is helped by detection of defects present on fruit peel. As there is a great demand for high-quality fruits in the market, the task of defect detection in fruit is very vital in the agricultural industry. However, defect detection by the human is labour-intensive and time-consuming. The proposed methodology is useful in supermarkets for automatic sorting of fruits from a set of different kinds of fruits. This system minimizes error and also speeds up the time of processing. The objective of this work is to present a novel method to detect surface defects of fruit using RGB images. The proposed method uses pre-processing, segmentation, edge-detection and feature extraction to classify the fruit as defected or fresh